Czytanie Krasickiego w Dubiecku (i trochę historii) - Pusz, Wiesław (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
The article is a summary of a meeting of scholars of the Enlightenment literature, dedicated to the works by Ignacy Krasicki, which was held in May 2013 in Dubieck. The author also briefly discusses the history of Polish post-war research on the eighteenth-century literature.